Numerical Simulations of Large Martian Impact Ripples - Hezi Yizhaq; Jasper F. Kok; Simone Silvestro; Lior Saban; Itzhak Katra (Geosciences, 2022)
Ripples made from unimodal fine sands can grow much larger on Mars than on Earth, reaching wavelengths of 1–3 m and heights exceeding 1 dm. Smaller decimeter-wavelength ripples can be superimposed on them. Classification and origins of these bedforms have been debated. They have been interpreted as analogous to subaqueous ripples on Earth, or as aeolian impact ripples with a range of grain sizes that reach large maximum sizes on Mars. This study uses a mathematical model to evaluate the formation of large Martian ripples as aeolian impact ripples to further investigate this hypothesis. The model parameters were computed using COMSALT for 100 µm grains under shear velocity of 0.65 m/s, which is a reasonable shear velocity for sand transport on Mars according to recent estimations of threshold Martian winds. The numerical experiments utilize a large grid 8 m long. Experiments also evaluate the development of secondary small ripples between the large ripples from random perturbations. The numerical simulations show the evolution of ripple wavelength and height. According to the results, the time scale for the formation of the large ripples is about 2–3 years, which is a much longer time scale compared to terrestrial impact ripples. Small secondary ripples develop only if the space between the large ripples is sufficiently large.